Implementasi Pendidikan Karakter Religius dalam Pembelajaran Pendidikan Agama Islam di Sekolah Dasar Negeri 08 Kikim Barat - Pipit Meliani; Mohamad Joko Susilo (LaKaspia, 2025)
This study aims to analyze the implementation of religious character education in Islamic Religious Education (PAI) learning at the elementary school level, focusing on SDN 08 Kikim Barat. A descriptive qualitative approach was employed using observation, interviews, and documentation. The findings indicate that religious character education is implemented through the integration of religious values in PAI learning, teachers’ role modeling (uswah hasanah), and daily worship habituation. The main values developed include religiosity, discipline, and responsibility. Theoretically, the findings demonstrate the integration of modern character education theory proposed by Thomas Lickona with classical Islamic thought, particularly Al-Ghazali’s concept of tazkiyah al-nafs and Ibn Miskawaih’s moral habituation. The theological foundation of religious character formation refers to Qur’an Surah Luqman verse 17. This study also reveals a structural gap between value formation at school and the home environment due to limited parental involvement. Furthermore, a positive correlation is found between students’ religious character and their mastery of PAI learning. The study concludes that successful religious character education requires sustained synergy between schools and families